Cartas d'eus: cartografias afetivas com Linn da Quebrada - Freitas, Leandro Leal de (Universidade Federal de São Carlos, 2020)
What learns and how I produce it them on the research path from and through the meetings with Linn da Quebrada? What possible worlds are created/fabled from this cartographic experimentation? Implied in a certain context and sensitive to the forces that cross and affect, what maps do I build from and with these encounters with subjectivity-rhizome-Linn? How to re-invent one (another) sensitivity education and operate with body-knowledge? How to make writing a productive escape machine that creates and invents and fabula and produces other possible worlds, other ways of inhabiting existential territories? Devir-trava, learn affected: existential, poetic and creative spellings. New narrative policies: producing possible ones that increase lifepower. Re-existence.
Letters d’eus: affective cartography with Linn da Quebrada
Keywords: Linn da Quebrada; Cartografias afetivas; Saber-do-corpo; Afetos; Affective cartography; Body-knowing; Affections; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO